(untitled) (Journal of the College of Basic Education, 2022)
This paper is an attempt to investigate linguistic strategies of ideological manipulation in selected speeches of Iraqi politicians after 2003. The analysis focuses on identifying and describing the linguistic tools employed in the data .Furthermore, it tackles the social function of language practice and power in political discourse. To this effect, the researcher, specifically, analyzes the concept of Federalism according to two contradictory ideologies. To fulfill this task , the researcher adopts Van Dijk’s socio-cognitive model (1995b;2006a ). Based on the results of the analysis, the study revealed that there is a number of linguistic strategies to demonstrate ideological manipulation : fallacy , euphemism , lexical repetition ,compassion –move, warning and the like. The study arrived at the following conclusions: (1)linguistic manipulation can be considered an influential instrument of political speeches because political discourse is basically focused on persuading people to take major decisions; and (2) Language plays a vital ideological role because it is a tool by which the politicians can convey their agendas to the public employing the whole potentialities and intricacies of English to accomplish their objectives